2022
DOI: 10.1186/s12888-022-03948-6
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of cannabis use for insomnia in depression and anxiety in a naturalistic sample

Abstract: Background Little is known about cannabis use for insomnia in individuals with depression, anxiety, and comorbid depression and anxiety. To develop a better understanding of distinct profiles of cannabis use for insomnia management, a retrospective cohort study was conducted on a large naturalistic sample. Methods Data were collected using the medicinal cannabis tracking app, Strainprint®, which allows users to monitor and track cannabis use for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Indica strains typically contain a higher ratio of CBD to THC, whereas Sativa strains typically contain a higher ratio of THC to CBD. Predominantly Indica or Indica hybrid strains were found to be subjectively more effective than Sativa or CBD only strains [6 ▪ ,11]. Also, the combination CBD plus THC had higher perceived improvement in insomnia versus CBD or THC alone [6 ▪ ].…”
Section: Cannabis Products and Insomniamentioning
confidence: 90%
“…Indica strains typically contain a higher ratio of CBD to THC, whereas Sativa strains typically contain a higher ratio of THC to CBD. Predominantly Indica or Indica hybrid strains were found to be subjectively more effective than Sativa or CBD only strains [6 ▪ ,11]. Also, the combination CBD plus THC had higher perceived improvement in insomnia versus CBD or THC alone [6 ▪ ].…”
Section: Cannabis Products and Insomniamentioning
confidence: 90%
“…There is emerging evidence that cannabis may have pharmacological properties that could be therapeutic in patients with BD (Ashton et al, 2005) and depression (Kuhathasan et al, 2022). Only about one‐third of people with BD respond to lithium (Rybakowski, 2014) and there is limited good quality evidence supporting other mood stabilizing medications, carbamazepine, valproate (Mitchell, 2008) and lamotrigine (Ng et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a naturalistic sample of individuals who self-reported using cannabis to cope with insomnia, cannabis use was perceived to help with sleep (Kuhathasan et al, 2021). This also appears to be the case among individuals with mental health problems, as in a recent study of individuals who self-reported using cannabis to cope with insomnia symptoms and comorbid depression and anxiety, cannabis use was perceived to help with sleep (Kuhathasan et al, 2022).…”
Section: The Multifaceted Relationship Between Insomnia and Cannabis Usementioning
confidence: 94%